Behov av managementverktyg i mjölkproduktionen - Zonabend, Emelie (2008)
For the company to work well, it is necessary with a good economy, a high qualitative production and a well working system concerning the environment: the whole cycle on the farm needs to be working. At the same time, debaters about the environmental impacts are also requiring higher demands for the dairy farmers and therefore also the management programs. Management programs for feed evaluation calculations have been more developed over the years. Big amounts have been invested in the new feeding system with NorFor, but no one seems to have asked the dairy farmers what they themselves want to spend their money on, and what they need help with. For the dairy farmers it is necessary that the whole company is controlled in the right way, and much more than just feed evaluation is included in this. The aim with this final thesis is to illuminate those aspects where the dairy farmers themselves believe that they need support, within the areas of economy, production and environment, and also to see if the management tool NorFor Plan can give the support that is requested.